AN ECONOMIC ANALYSIS OF CUSTOMERS’ ATTRACTION TOWARDS SUPER MARKET: A CASE STUDY - Chengappa, Reshma (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A Supermarket, a large form of the traditional grocery store, is a self-service shop offering a wide variety of food and household products, organized into aisles. It is larger and has a wider selection than a traditional grocery store, but is smaller and more limited in the range of merchandise than a hypermarket or big-box market. Eastern market is one the famous supermarkets in Mysuru city. It is located in Rajiv Nagar, and established in December 2011. The Objective of this paper is to examine the factors attracting customers towards Eastern Market. The identified factors attracting customers towards Eastern Market are convenient location, ambience, efficient process and promotional facilities, value for money and value for time of Eastern Market. The manual method was adopted for data processing and data analysis is done with the help of SPSS software. Statistical techniques like Z test of proportions was used to test the impact of convenient location and ambience, chi-square test is used to test the impact of efficient process and promotional facilities, value for money and value for time of Eastern Market, and spearman’s rank correlation (rho) is deployed to test whether there is a positive correlation between the opinions of customers regarding the factors which attract customers towards Eastern Market and the opinion of manager of Eastern Market, with these hypotheses tests it has become evident that the identified factors which attracts customers towards Eastern Market are significant and proved with 0.01% and 0.05% significance level.